Mycoremediation to Remove Heavy Metal Pollution in Post-Mining Areas for Farmland Utilization - Riza Zainuddin Ahmad (Indonesian Center for Animal Research and Development, 2018)
The agriculture land including farmland is decreasing caused by conversion to industrial area and settlement, therefore post-mining area is used to be farmlands. The utilization of post-mining area causes serious health problem in animals and humans due to heavy metal waste pollution (Ag, As, Cd, Co, Cr, Cu, Hg, Ni, and Pb). Efforts to overcome the pollution of heavy metals on farms can be carried out by preventing and controlling waste in post-mining and industry areas. There are several mycoremediation methods to recover heavy metal polluted land such as biosorption, bioaccumulation, bioprecipitation, bioreduction, and bioleaching. Mycoremediation is a process to remove pollutants or heavy metals from soil using potential fungi (Aspergillus flavus, Penicillium sp, Fusarium sp, Saccharomyces cerevisiae). Mycoremediation is chosen due to economical cost, efficient, and environmentally friendly.